1988
DOI: 10.1172/jci113622
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro human muscle preparation suitable for metabolic studies. Decreased insulin stimulation of glucose transport in muscle from morbidly obese and diabetic subjects.

Abstract: We have developed an in vitro muscle preparation suitable for metabolic studies with human muscle tissue and have investigated the effects of obesity and non-insulin-dependent diabetes mellitus (NIDDM) on glucose transport. Transport of 3-0-methylglucose and 2-deoxyglucose was stimulated approximately twofold by insulin in muscle from normal nonobese subjects and stimulation occurred in the normal physiological range of insulin concentrations. In contrast to insulin stimulation of 3-0-methylglucose and 2-deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
161
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(172 citation statements)
references
References 24 publications
8
161
1
1
Order By: Relevance
“…Very thin muscle fiber strips were incubated in vitro to make metabolic measurements, including rates of glucose transport, glycogen synthesis, and glycolysis. 6 With this preparation, we demonstrated that insulin stimulation of glucose transport, which is the limiting step in glucose utilization, is depressed in muscle7 of morbidly obese patients with or without diabetes. The degree of insulin resistance is correlated with the degree of obesity up to a body mass index of approximately 30,8 after which there is little further change.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Very thin muscle fiber strips were incubated in vitro to make metabolic measurements, including rates of glucose transport, glycogen synthesis, and glycolysis. 6 With this preparation, we demonstrated that insulin stimulation of glucose transport, which is the limiting step in glucose utilization, is depressed in muscle7 of morbidly obese patients with or without diabetes. The degree of insulin resistance is correlated with the degree of obesity up to a body mass index of approximately 30,8 after which there is little further change.…”
Section: Discussionmentioning
confidence: 92%
“…We have documented 43 episodes of hypoglycemia in 35 patients, 6 of whom were from the NIDDM cohort, 1 from those with insulin-dependent diabetes mellitus, 8 DAY OUT FROM GASTRIC SURGERY be troublesome, with blood glucose levels as low as 27 mg/dL. We have treated these without therapeutic intervention, urging these patients to carry sugar, and most were self-limited, with corrections occurring usually within 1 year.…”
Section: Control Of Diseasementioning
confidence: 99%
“…Glucose homeostasis is maintained when glucose production and utilization are in balance. Skeletal muscle, the main site for glucose disposal [1] , displays decreased glucose uptake when insulin resistance occurs in T2DM patients [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…While insulin signalling to IRS-1 and PI 3-kinase is impaired in skeletal muscle from Type 2 diabetic patients, phosphorylation of the mitogen-activated protein kinase (MAPK) extracellular regulated kinase (ERK1/2) is normal [4,5], suggesting diversity in insulin action along metabolic and mitogenic signalling pathways in Type 2 diabetes. Impaired insulin-mediated whole body glucose uptake in Type 2 diabetes [1,2,3,4,5], as well as in several other insulin resistant states such as morbid obesity [6,7], polycystic ovary syndrome [8], gestat-MAPK's are part of a large family of related serine/threonine protein kinases that include the ERK1/2, p38 MAPK and c-jun and form a major signalling system to facilitate signal transduction to appropriate genomic, rather than direct metabolic responses [16,17]. However, p38 MAPK has recently been proposed to play a metabolic role in the regulation of insulinstimulated glucose transport by either altering the "intrinsic activity of GLUT4" or by facilitating the transition of GLUT4 from an occluded to a fully activated (exposed) state at the plasma membrane [18].…”
mentioning
confidence: 99%